Mi lesz veled területfejlesztés? - Faragó, László (Tér és Társadalom, 1992)
After reporting objectively about the results of regíonal development during the last two years, the author speaks about the „attacks" against the institutions of regional development, and the regional development activities themselves. Afterwards, the author lists some of the actual tasks in order to prove that these activites are more than up-to-date today. At the collapse of existing socialism, we could not speak about modern regional development in Hungary. After the transformation into a new regime, the case of regional development was different from the traditional sectors, as the second had the chance to keep their existing market positions, or to withdraw parallel with the decrease of central governmental positions, or to redistribute the resources according to the new division of labour. In contrast to this, regional development has to fight for the conditions required to fulfill the different tasks amidst the general lack of resources and budget restrictions. After the transformation into a new regime, the conditions have temporarily become even worse. Environmental protection, nature reservation and regional development were upgraded, while the personal and financial conditions were not granted for the portfolio responsible for the fulfilment of the tasks. As a clear consequence of the misbelief about planning, namely that it is primarily and basically the means of socialism to act, the credit of regional planning has to be re-established. The introduction of the independence of local authorities temporarily strengthens disintegration, which considerably increases the governmental duties as well. In the Summer of 1992, regional planning was attacked also by the environmentalists. The above swaying of the public díd not really favour a situation when both professions (environmental protection and regional development) can equally use the ob ovo advantages of working together within one institution and realize the concept of „environment and development" (announced by the conference in Rio). The author begins the list of the most urgent tasks with the need to establish proper legal regulations. The two-year operation of the government, the already passed legislations and the developing frightening phenomena prove that modern regional thinking cannot prevail without proper legal regulations. The law on regional development has to be passed. The related preparations are only the first foundational steps of a long process. The concrete, short- and medium-term tasks of regional development, and – from time to time – the greater development projects have to be included in the regional policy of the government. The author considers the establishment of the necessary network of institutions the second most important thing to do. Stemming from the multi-sector character of regional development, a National Regional Development Council has to be set up in order to guarantee democratic decision-making in regional issues, and to facilitate the fulfilment of its coordinating functions. Furthermore, the most important task of institutionalization is to put an end to the lack of medium-level institutional network. In harmony with our intention to join the Common Market, it seems to be rational to develop structures that meet European expectations. Statistical units of observation have to be created on two levels between the settlements and the government, and these, at the same time, are levels of regional development. There is a clear need to create 6-8 macro-regional units, and at the lower level, strengthening the roles of counties, or granting similar roles to the agglomerations have to be considered. Finally, the reader learns about the most important planning tasks of regional development, and the government projects aiming at improving the underdeveloped regions.